Preparation for Life/ Corporate Communications & International Relations Office, UiTM - UiTM, Jabatan Komunikasi Korporat & Perhubungan Antarabangsa (Corporate Communications & International Relations Office, UiTM, 2006)
What our founding fathers did could be compared to planting a seed. Physically and physiologically, a full grown tree is completely unlike the seed that it has come from. UiTM is similar to that tree. Careful nurturing, aided by the vision and foresight of our political leadership has enabled the university to enter into its golden era of maturity. The university today encompasses 22 faculties and 14 branch campuses with a total student population of about 100,000. Our world today is drastically different from that of our founding fathers. The inexorable march of history, particularly after September I I, has torn down many old certainties and put us at the threshold of new possibilities, new challenges, new threats and new opportunities. In these "interesting times", we must seize every opportunity that comes our way in the spirit of reinventing our lives, our institutions, and our innovativeness so as to be competitive and productive on a scale never seen before.